Pengaruh Iklim Sekolah dan Disiplin Diri terhadap Hasil Belajar Siswa SMA Swasta di Jakarta - Djumiati Djumiati; Ida Ayu Gede Yadnyawati; Muljadi Muljadi (Dhammavicaya : Jurnal Pengkajian Dhamma, 2024)
One of the important topics in education is the factors that influence student learning outcomes. This study aims to analyze the influence of school climate and self-discipline on student learning outcomes in Jakarta Private High Schools. The independent variables in this study are school climate (X1) and self-discipline (X2), while the dependent variable is learning outcomes (Y). This study uses a quantitative approach with a correlation method to test the relationship between variables. The sample of this study consisted of 171 respondents selected from a population of 300 students using a non-probability sampling technique, based on the Slovin formula. Data collection was carried out through a questionnaire with a Likert scale consisting of four answer choices, and distributed using Google Forms. Hypothesis testing was carried out using SPSS 20.0 for Windows, with validity testing using Product Moment Correlation and reliability using the Cronbach Alpha formula. The results showed that school climate has a positive influence on student learning outcomes with a correlation coefficient of 0.765 and a determination coefficient of 0.585. Self-discipline also has a positive influence on student learning outcomes with a correlation coefficient of 0.716 and a determination coefficient of 0.512. Overall, school climate and self-discipline have a positive influence on learning outcomes with a correlation coefficient of 0.812 and a determination coefficient of 0.659. The regression obtained is Ŷ1.2 = -6.980 + 0.160X1 + 0.105X2. These findings indicate the importance of improving school climate and self-discipline to optimize student learning outcomes.